Perinatal Imaging in Partnership with Families (PIPKIN): Longitudinal cohort study protocol - Kaili Clackson; Dianna Ilyka; Borja Blanco; Staci Meredith Weiss; Isobel Greenhalgh; Maria Rozhko; Laura Carnevali; Matthew Weatherhead; Xiangyi Ma; Beyza Ustun-Elayan; Ezra Aydin; Noelia Corral Ferre; et al. (PLoS ONE, 2025)
While advances in behavioural and neuroimaging methods suitable for use with infants have greatly increased our understanding of infant brain function, cognition and behaviour in recent years, relatively little is known about the rapid period of development during the last trimester of pregnancy and first weeks and months after birth, as well as the roles that the social environment and stress play in shaping this development. This protocol paper outlines The UK Perinatal Imaging in Partnership with Families (PIPKIN) Study, a unique, multi-method, longitudinal cohort study investigating the early development of fetal and infant neurocognitive function and behaviour, and how the infant’s social and family environment shapes this development. The study follows families from a range of socio-economic backgrounds who participate at ten timepoints, from the third trimester of pregnancy until their infant is nine months old, with three visits taking place during the infant’s first postnatal month. The study harnesses recent methodological advances coupled with the drive for more ecologically valid data collection by undertaking many of these visits in families’ homes. Methods include measures of fetal behaviour using 4D ultrasound scanning; infant brain imaging using fNIRS and EEG; a full-day video recording of the home environment from the infant’s perspective, with physiological measures; measures of recent stress in both infant and mother; questionnaires relating to the home environment as well as parents’ feelings, attitudes, health and parenting routines; and standardised measures of infant behaviour and development. Specific aims are to investigate: i) individual differences in basic sensory, behavioural and motor processing between late prenatal and early postnatal periods; ii) rapid change in cortical functions over the first month, particularly for brain networks that support social behaviour; iii) effects of social interaction on developing brain function; and iv) individual differences in developmental trajectories associated with poverty-related contextual factors.